2015
DOI: 10.3727/096368914x682125
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Spinal Cord Injury-Induced Bladder Fibrosis Using Mesenchymal Stem Cell Transplantation into the Bladder Wall

Abstract: Experiments on spinal cord injury (SCI) have largely focused on the transplantation of stem cells into injured spinal cords for motor recovery while neglecting to investigate bladder dysfunction. The present study was performed to investigate the effect of B10 human mesenchymal stem cells (hMSCs) directly transplanted into the bladder wall of SCI rats and to determine whether they are capable of inhibiting collagen deposition and improving cystometric parameters in SCI rats. Forty 6-week-old female Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Scale bars represent 1 μm in (i) and (ii) tissue when we have used a graft seeded with cells for reconstruction of the bladder defect (Yudintceva et al, 2016). Other groups obtained similar data when SPION-labelled stem cells were applied (Lee et al, 2015;Yun & Ja, 2007). Presumably, in these cases, the area of the defect limits the migration and the cells reside only in the implantation zone (Geburek et al, 2016).…”
Section: Discussionmentioning
confidence: 65%
“…Scale bars represent 1 μm in (i) and (ii) tissue when we have used a graft seeded with cells for reconstruction of the bladder defect (Yudintceva et al, 2016). Other groups obtained similar data when SPION-labelled stem cells were applied (Lee et al, 2015;Yun & Ja, 2007). Presumably, in these cases, the area of the defect limits the migration and the cells reside only in the implantation zone (Geburek et al, 2016).…”
Section: Discussionmentioning
confidence: 65%
“…Previously, Lee et al reported that SPION-labeled MSCs could be tracked by MRI in the bladder. 42 Intriguingly, we observed the presence of labeled BMSCs only in the graft, which might indicate that introduced cells usually stay in the place of implantation without migration into other zones. Subsequent confocal microscopy of bladder cryosections confirmed the presence of the nanoparticle-labeled cells throughout all layers of the wall without any labeled cells in native bladder tissues ( Figure 8).…”
mentioning
confidence: 89%
“…Improvement of bladder dysfunction by stem cell therapy was observed in experiments in spinal cord injury animal models [26]. Treating complications such as bladder dysfunction is important for improving the patient's quality of life.…”
Section: Stem Cell Therapymentioning
confidence: 99%